Spinal Tuberculosis (Pott's Disease) - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2012)
Researchers at Great Ormond Street Hospital for Children and Institute of Child Health, London, UK reviewed their experience of childhood spinal tuberculosis (TB) over a 15-year period (1995-2010).